Evidence for introgressive hybridization of wild black‐necked pheasant with the exotic ring‐necked pheasant during the past 50 years in the Hyrcanian zone, an integrative molecular and morphological approach. (18th November 2021) - Aliakbari, Zohreh; Kayvanfar, Nasrin; Rajabi‐Maham, Hassan; Ghasempouri, Seyed Mahmoud
Abstract: Hybridization with non‐native‐related taxa, especially with introgression, is a major conservation problem, as it may disturb local adaptations, resulting in population decline and biodiversity loss. It is important to identify hybrid individuals, which can be difficult to break up morphologically. Using morphometric and genetic approaches [multivariate analysis, microsatellites, and amplified fragment length polymorphism (AFLP)], this research attempts to classify the interaction and the prevalence of introgressive hybridization in four native pheasant subspecies of Phasianus colchicus with non‐native P. c . torquatus . According to principal component analysis and canonical discriminant function results, hybrid individuals are placed between these two major groups of native and exotic birds. Also, we assessed the population structure, genetic variation, and gene flow between native subspecies and exotic pheasants using 16 microsatellite loci in 129 samples. Our findings revealed that hybridization occurred between two native subspecies, P. c. talischensis and P. c. persicus, and exotic subspecies ( P. c. torquatus ). Observation of hybrids in P. c. persicus were almost three times higher than P. c. talischensis . The levels of the genetic variation within and among the natural populations were investigated using the AFLP markers method to identify hybrids. A total of 202 distinct bands were amplified using four primer combinations, with 179 of them being polymorphic. AMOVA analysis revealed a low degree of genetic differentiation among the populations. The hybrid samples were closely related to the P. c. talischensis and P. c. persicus populations, according to the UPGMA clusters and discriminant analysis of principal components. It appears that disruption of gene flow between pheasant populations in the Hyrcanian zone is a serious issue. The data from molecular markers prompted us to raise a concern about the genetic integrity in some native subspecies in the Iranian plateau. As a result, a clear cut‐level can now be used to differentiate the hybrids, which is also supported by morphological evidence. A direct relationship was found between farmed pheasants and hybrid frequency. Farmed individuals should be closely monitored, and non‐native taxa should not be released into the wild. Abstract : There is molecular evidence that exotic pheasant subspecies hybridize with wild subspecies in the Hyrcanian central green belt of the southern Caspian basin. Almost all hybrid specimens were found in persicus or talischensis subspecies habitats, areas where there were several traditional pheasant farms in recent years. More than a thousand ring‐necked pheasant farms have been operating in Iran since the first exotic pheasants arrived at least 50 years ago that always release several pheasants into the wild accidentally.